PSYCHIATRIC COMORBIDITIES IN GASTROESOPHAGEAL REFLUX DISEASE: A PROSPECTIVE OBSERVATIONAL STUDY USING STANDARDIZED PSYCHIATRIC SCALES - M Rangapriya; Mohammed Rimshad P; R Manivannan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Gastroesophageal reflux disease (GERD) is a chronic gastrointestinal illness that is more and more linked with mental disorders like depression and anxiety, and even sleep disturbances. These conditions that come together worsen the symptoms, decrease the quality of life (QoL), and remain a hurdle in treatment. The goal of this research was to measure the extent of the psychiatric comorbidities in the GERD patients and their severity, as well as to correlate the comorbidities with GERD severity and QoL.Methods: A prospective observational study was performed that included 100 GERD patients that were clinically confirmed at Almas Tertiary Care Hospital, Kerala. The GERD severity of the patients was measured by means of the GERD-Q scale. The measures of depression, anxiety, sleep disturbances, and QoL were made with PHQ-9, GAD-7, PSQI, and the GERD-HRQL scales, respectively. The data were processed by using SPSS; correlations were established via Pearson's test.Results: Depression, anxiety, and sleep disturbances were the psychological conditions that suffered from the highest prevalence among GERD patients. 57% of the patients suffered from depression, 71% from anxiety, and 48% from sleeping problems. The QoL of the patients was reported to be very poor in the case of 79%. The GERD severity had a strong positive correlation with depression (r = 0.881, p < 0.001), anxiety (r = 0.876, p < 0.001), and sleep disturbances (r = 0.831, p < 0.001). The age of the patients (41–60 years), alcohol use, hypertension, diabetes, longer GERD duration, and severe GERD were significant predictors..Conclusion: Psychiatric comorbidities are highly prevalent in GERD and significantly worsen QoL. Routine psychiatric screening and integrated management may improve both psychological and gastrointestinal outcomes.